Pengaruh Task Commitment Terhadap Pembelajaran Tahfidz Al Quran - Niamul Karim (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This research aims to determine the effect of task commitment on learning Tahfidz Al-Quran for Class VII G at Mts Al Manar Nganjuk. This type of research is quantitative research using survey methods. The population in this study were class VII G students at MTs Al Manar Nganjuk. The sample in this research was all students in class VII G at MTs Al Manar Nganjuk, totaling 21 people. The sampling technique is a saturated sampling technique. The instruments used are the task commitment test scale and the acquisition of tahfidz during learning. The data analysis techniques used are person correlation and regression in SPSS 16.0 software. The results of the research area. Most of the students in class VII G have task commitment in the high category with 36.28. b. Most of the students in class VII G in learning tahfidz for Â± 3 months achieved memorization success in the very high category of 38.1% and the high category of 38.1%. and there were 3 students who were able to complete the memorization target 100%. c. There is a positive influence of task commitment on tahfidz learning as much as 73.2%.